Prognostic Model of D2 Radical Gastrectomy Combined with Neoadjuvant Chemotherapy for Gastric Cancer - Wang G; Tan Y; Jiang Y; Liu J; Su Y; Sun Z; Liu B (Dove Medical Press, 2023)
Guangjun Wang,1,* Yinghua Tan,2,* Yongjie Jiang,1 Jia Liu,1 Yuanhui Su,3 Zhengang Sun,4 Bo Liu3,5 1Department of General Surgery, Qingdao West Coast New Area Central Hospital, Qingdao, Shandong, People's Republic of China; 2Department of Paediatrics, Qingdao West Coast New Area Central Hospital, Qingdao, Shandong, People's Republic of China; 3Department of General Surgery, Lanzhou University Second Hospital, Lanzhou, Gansu, People's Republic of China; 4Department of Spine Surgery, Qingdao West Coast New Area Central Hospital, Qingdao, Shandong, People's Republic of China; 5Department of Gastrointestinal Surgery, the Affiliated Hospital of Qingdao University, Qingdao, Shandong, People's Republic of China*These authors contributed equally to this workCorrespondence: Bo Liu, Email drliubo@outlook.comPurpose: The AJCC (the American Joint Committee on Cancer) ypTNM (post-neoadjuvant pathologic stage group) staging was established based on patients with lymphadenectomy scope less than D2 and did not include ypT0N0 patients with pathologically complete response (PCR). The purpose of this study was to construct a survival predictive model for gastric cancer patients after neoadjuvant chemotherapy and gastrectomy combined with D2 lymphadenectomy.Patients and Methods: The multicenter data of 838 gastric cancer patients who received neoadjuvant chemotherapy and gastrectomy combined with D2 lymphadenectomy were analyzed retrospectively. These dual center patients were divided into training (n = 671, the Affiliated Hospital of Qingdao University) and validation (n = 167, Qingdao West Coast New Area Central Hospital) cohorts. Based on training cohort, univariate and multivariable COX regression analyses were performed to select the clinicopathological characteristics significantly correlating with overall survival and construct a nomogram. Based on training and validation cohorts, the distinguishing and calibrating capabilities of nomogram was evaluated by the receiver operating characteristic (ROC) curve, Harrell's concordance index (C-index), decision curve analysis (DCA) curve and calibration curve.Results: Platelet-to-lymphocyte ratio (PLR), pathologic stage after neoadjuvant treatment: ypT and ypN stage, tumor regression grade (TRG) became independent variables intimately related to the prognosis and was used to construct nomograms of 3/5-year prognosis. The nomograms showed an accuracy in predicting OS (overall survival) rate, with area under the ROC curve (AUC) of 0.818 (95% CI = 0.753~0.883) and C-index of 0.801 (95% CI = 0.744~0.858) in validation cohort. Calibration curves showed satisfactory agreement between nomogram prediction and actual result, and DCA curves indicated the large positive net benefit and excellent clinical usefulness of nomogram.Conclusion: This study successfully developed a nomogram to predict overall survival of gastric cancer patients after neoadjuvant chemotherapy and gastrectomy combined with D2 lymphadenectomy, which might have excellent predictive performance and clinical application value.Keywords: gastric cancer, neoadjuvant therapy, gastrectomy, nomogram, survival analysis